When Vulnerable Narcissists Take the Lead: The Role of Internal Attribution of Failure and Shame for Abusive Supervision - Braun, Susanne (Journal of business ethics, 2025)
Research to date provides only limited insights into the processes of abusive supervision, a form of unethical leadership. Leaders’ vulnerable narcissism is important to consider, as, according to the trifurcated model of narcissism, it combines entitlement with antagonism, which likely triggers cognitive and affective processes that link leaders’ vulnerable narcissism and abusive supervision. Building on conceptualizations of aggression as a self-regulatory strategy, we investigated the role of internal attribution of failure and shame in the relationship between leaders’ vulnerable narcissism and abusive supervision. We found across three empirical studies with supervisory samples from Germany and the United Kingdom (UK) that vulnerable narcissism related positively to abusive supervision (intentions), and supplementary analyses illustrated that leaders’ vulnerable (rather than grandiose) narcissism was the main driver. Study 1 (N = 320) provided correlational evidence of the vulnerable narcissism-abusive supervision relationship and for the mediating role of the general proneness to make internal attributions of failure (i.e., attribution style). Two experimental studies (N = 326 and N = 292) with a manipulation-of-mediator design and an event recall task supported the causality and momentary triggers of the internal attribution of failure. Only Study 2 pointed to shame as a serial mediator, and we address possible reasons for the differences between studies. We discuss implications for future studies of leaders’ vulnerable narcissism as well as ethical organizational practices.